Snowpack Change From 1982 to 2016 Over Conterminous United States - Xubin Zeng; Patrick Broxton; Nicholas Dawson (Geophysical Research Letters)
Abstract Snow water equivalent (SWE) variability and its drivers over different regions remain uncertain due to lack of representativeness of point measurements and deficiencies of existing coarse‐resolution SWE products. Here, for the first time, we quantify and understand the snowpack change from 1982 to 2016 over conterminous United States at 4‐km pixels. Annual maximum SWE decreased significantly (p < 0.05) by 41% on average for 13% of snowy pixels over western United States. Snow season was shortened significantly by 34 days on average for 9% of snowy pixels over the United States, primarily caused by earlier ending and later arrival of the season over western and eastern United States, respectively. October–March mean temperature and accumulated precipitation largely explain the temporal variability of 1 April SWE over western United States, and considering temperature alone would exaggerate the warming effect on SWE decrease. In contrast, temperature plays the primary role in the 1 April SWE variability over eastern United States.